Genital porokeratosis of Mibelli. Issue 6 (December 1995) - Neri, I; Marzaduri, S; Passarini, B; Patrizi, A
Abstract : Porokeratosis of Mibelli is a disorder of epidermal proliferation in which many different clinical forms can be distinguished. Two male patients with a localized type of porokeratosis limited to the genitalia are reported. Later in life they developed an annular skin lesion with peripheral keratotic ridge. The histological examination of a biopsy specimen showed the characteristic features of porokeratosis. There was no family history of similar skin disorders and the patients were not on any drugs. Genital porokeratosis is probably underdiagnosed and we believe that these patients should be followed up on account of the precancerous potential of this disease.